Modernist turn in Tragicomedy - Garbyal, Neha (International Journal of Psychosocial Rehabilitation, 2021)
This study examines the historical relationship between tragicomedy in the modern theatre and the play culture of Western consumer communities. When it comes to the variety of playwrights, it focuses on the work of Samuel Beckett, Harold Pinter and Sam Shepard. Their plays, debated, shed light on the forms of happiness, fear, work and corruption that dominate our daily lives. Tragicomedy is seen as unique in the playfulness and confusion of its opponents, and because of its silent vision of the apocalypse in the nuclear age.